Advanced borehole seismic imaging techniques for mineral exploration - Zulic, Sana (Curtin University, 2022)
The thesis examines the current VSP application in mineral exploration in Australia and identifies the challenges and studies in which domain these challenges could be mitigated. In particular, the advancements can be seen in the equipment domain, by applying DAS technology, and in the processing domain, by utilising the full-waveform inversion techniques. Finally, the thesis demonstrates how advanced VSP techniques address the identified challenges and introduces a high-resolution dataset to assist subsurface characterisation.